2015
DOI: 10.3389/fncel.2015.00373
|View full text |Cite
|
Sign up to set email alerts
|

Dual processing of sulfated steroids in the olfactory system of an anuran amphibian

Abstract: Chemical communication is widespread in amphibians, but if compared to later diverging tetrapods the available functional data is limited. The existing information on the vomeronasal system of anurans is particularly sparse. Amphibians represent a transitional stage in the evolution of the olfactory system. Most species have anatomically separated main and vomeronasal systems, but recent studies have shown that in anurans their molecular separation is still underway. Sulfated steroids function as migratory phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
(79 reference statements)
0
21
0
Order By: Relevance
“…Isogai et al (2011) extensively explored possible ligands for V1Rs by applying two-color in situ hybridization assays using probes against egr-1 (a marker for neuronal activation) and one specific receptor gene on VNO sections of individual mice that were exposed to variable stimuli. In this study, some V1Rs were shown to detect and discriminate distinct structural classes of sulfated steroids, which may act as sensitive reporters of the endocrine state in a broad range of vertebrates, including lamprey (Sorensen et al, 2005), goby (Murphy et al, 2001), cichlids (Cole and Stacey, 2006), tilapia (Keller-Costa et al, 2014) and amphibians (Sansone et al, 2015).…”
Section: De-orphanization Of V1rsmentioning
confidence: 90%
“…Isogai et al (2011) extensively explored possible ligands for V1Rs by applying two-color in situ hybridization assays using probes against egr-1 (a marker for neuronal activation) and one specific receptor gene on VNO sections of individual mice that were exposed to variable stimuli. In this study, some V1Rs were shown to detect and discriminate distinct structural classes of sulfated steroids, which may act as sensitive reporters of the endocrine state in a broad range of vertebrates, including lamprey (Sorensen et al, 2005), goby (Murphy et al, 2001), cichlids (Cole and Stacey, 2006), tilapia (Keller-Costa et al, 2014) and amphibians (Sansone et al, 2015).…”
Section: De-orphanization Of V1rsmentioning
confidence: 90%
“…An interesting study was recently published by Sansone et al (). The authors found that sulfated steroids are detected by olfactory and vomeronasal neurons in tadpoles of X. laevis .…”
Section: Discussionmentioning
confidence: 97%
“…The olfactory detection and neuronal processing of such multicomponent pheromones is a highly complex phenomenon, often simultaneously involving MOO and VNO. This interconnectivity of the two chemosensory systems is well studied in mammals (for review see Wyatt, ) and likely to occur in amphibians (Sansone et al ., ). Thirdly, neuronal activity of olfactory sensory cells is often dosage‐dependent.…”
Section: Discussionmentioning
confidence: 99%